A bromide-induced highly oriented low-dimensional Ruddlesden–Popper phase for efficient and stable perovskite solar cells. Issue 26 (29th June 2021) - Hu, Jianfei; Liu, Jin; Chen, Haoran; Ran, Xueqin; Zhang, Hui; Li, Ping; Song, Lin; Müller-Buschbaum, Peter; Xia, Yingdong; Chen, Yonghua
Abstract : A highly vertically oriented LDRP phase is achieved by introducing Br into BA lead halide perovskites, i.e., (C4 H9 NH3 )2 MA4 Pb5 Br x I16− x . The I–Br–I based PSCs show improved PCE (15.75% vs. 12.15%) and stabilities compared to the device with the pristine I–I–I system. Abstract : Low-dimensional Ruddlesden–Popper (LDRP) perovskites have attracted great attention due to their superior stabilities. However, these LDRP perovskites are required to grow vertically with respect to the substrates to enable efficient charge transport for highly efficient and stable perovskite solar cells (PSCs). Herein, we introduce a strategy to form a highly vertically oriented LDRP phase by introducing bromide (Br) into organic ammonium spacer of butylamine (BA) lead halide perovskites, i.e., (C4 H9 NH3 )2 MA4 Pb5 Br x I16− x . The LDRP perovskites with a small amount of Br (I–Br–I system with Br : PbI2 = 2 : 5 (molar ratio)) show the best abilities to form high-quality thin films and excellent vertical crystalline orientation, which facilitates charge transport and thus leads to highly efficient PSCs. As a result, a high champion PCE of 15.75% is achieved for the I–Br–I LDRP PSC compared to that of the pure iodine (I–I–I) device (12.15%). This work provides a new way to achieve efficient and stable LDRP PSCs.